Peran Jaringan Inovasi Terhadap Pertumbuhan Usaha Mikro Kecil Menengah di Indonesia - Pardiyono, Ragil; Jahny Sastradiharja; Gianti Puspawardhani; Oviyan Patra; Hendi Suryana (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to test network innovation. The proven network innovation model is the Kaplan & Winby model, namely associations, suppliers, customers and government. Based on references from several countries, none have discussed network innovation for MSMEs affected by the Covid pandemic. So this study will test the innovation of the role of networks for the revival of MSMEs after the pandemic. Data was taken based on a questionnaire on MSMEs in the Bandung City area. Then the data processing uses the SPSS software application. Based on the results of data processing, the results obtained that partially based on the coefficient values of the association coefficients, suppliers, customers and show a direct influence on the Economic Recovery of MSMEs. Meanwhile, based on t count by taking a significance level of 5%, it is proven that the test is not significant or there is an influence from suppliers on the Economic Recovery of MSMEs. Simultaneously, it was obtained that 57.76% of the Economic Recovery of MSMEs was influenced by the variables of suppliers, associations, consumers and government. So it can be concluded that there is a linear relationship between suppliers, associations, consumers and the government on the Economic Recovery of MSMEs (Y) with a coefficient of determination (R2) = 57.76% or 57.76, this can also be interpreted that the influence of variables outside the model is small, namely 1-R2 = 1-57.76% = 42.24% (error).